Role of Land Deed Officials (PPAT) in Protecting the Rights of Parties in the Creation of Deeds of Sale and Purchase of Land Rights - Simanjuntak, Kristi Warista (JUSTISI, 2025)
The aim of this study is to examine the role of land deed officials in sales and purchase transactions and the process of transferring ownership certificates, as well as to identify the obstacles encountered in practice. This study uses a socio-legal approach with a qualitative descriptive method, combining positive law analysis and interviews with land deed officials. The study also highlights the authority and responsibilities of land deed officials, including their obligations before and after the deed is drawn up, as well as the professional ethics regulated by the professional organization Association of Land Deed Officials (PPAT). The novelty of this research lies in its emphasis on the practical challenges faced by land deed officials in ensuring legal certainty in the sale and purchase of land and/or building rights, which has not been widely discussed in previous literature, especially regarding the mismatch between existing legal procedures and technical and administrative obstacles encountered in the field. The results of the study indicate that land deed officials play a very important role in ensuring the smooth sale and transfer of certificates through several stages, such as providing information, checking the completeness of documents, verifying the validity of certificates, and registering with the National Land Agency (BPN). However, the obstacles often encountered are the many requirements that must be met, high costs, lengthy processes, and inadequate facilities and technology. Solutions to overcome these problems include providing guidance to the public, collaborating with professional organizations to review tax costs, and improving facilities and technology that support the process of deed and certificate transfer. In concluded despite various challenges, the role of land deed officials remains crucial in maintaining legal certainty in the sale and purchase of land and/or building rights, with relevant solutions to simplify the process for the public.